2020
DOI: 10.1097/01.asw.0000655492.40898.55
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Oral Nutrition Supplement Containing Collagen Peptides on Stratum Corneum Hydration and Skin Elasticity in Hospitalized Older Adults: A Multicenter Open-label Randomized Controlled Study

Abstract: OBJECTIVE The purpose of this randomized open-label study was to investigate the effect of an oral nutrition supplement containing collagen peptides on stratum corneum hydration and skin elasticity. METHODS The study protocol was registered at the UMIN Clinical Trials Registry (UMIN 000027347). Once-a-day oral administration of a nutrition supplement containing collagen peptides (10.0 g) was instituted in 39 inpatients 65 years or older who were assigned to either the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 24 publications
(22 reference statements)
1
27
0
5
Order By: Relevance
“…(2015), Choi et␣al. (2014), and Nomoto and Iizaka (2020), 38–40 and with respect to incomplete data in the results by Nomoto and Iizaka (2020), Proksch et␣al. (2014a), and Schwartz et␣al.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…(2015), Choi et␣al. (2014), and Nomoto and Iizaka (2020), 38–40 and with respect to incomplete data in the results by Nomoto and Iizaka (2020), Proksch et␣al. (2014a), and Schwartz et␣al.…”
Section: Resultsmentioning
confidence: 90%
“…A methodological assessment of the quality of RoB was performed using the RoB-2 tool. The assessment of RoB at the domain level revealed a low RoB for most studies, as shown in (2019), 17,40,41 as shown in Figure 10.…”
Section: Biasmentioning
confidence: 90%
See 3 more Smart Citations